16x-112⋅(x-1)=12

Simplify each term.

Combine 16 and x.

x6-112⋅(x-1)=12

Apply the distributive property.

x6-112x-112⋅-1=12

Combine x and 112.

x6-x12-112⋅-1=12

Multiply -112⋅-1.

Multiply -1 by -1.

x6-x12+1(112)=12

Multiply 112 by 1.

x6-x12+112=12

x6-x12+112=12

x6-x12+112=12

To write x6 as a fraction with a common denominator, multiply by 22.

x6⋅22-x12+112=12

Write each expression with a common denominator of 12, by multiplying each by an appropriate factor of 1.

Multiply x6 and 22.

x⋅26⋅2-x12+112=12

Multiply 6 by 2.

x⋅212-x12+112=12

x⋅212-x12+112=12

Combine the numerators over the common denominator.

x⋅2-x12+112=12

Subtract x from x⋅2.

Reorder x and 2.

2⋅x-x12+112=12

Subtract x from 2⋅x.

x12+112=12

x12+112=12

x12+112=12

Subtract 112 from both sides of the equation.

x12=12-112

To write 12 as a fraction with a common denominator, multiply by 66.

x12=12⋅66-112

Write each expression with a common denominator of 12, by multiplying each by an appropriate factor of 1.

Multiply 12 and 66.

x12=62⋅6-112

Multiply 2 by 6.

x12=612-112

x12=612-112

Combine the numerators over the common denominator.

x12=6-112

Subtract 1 from 6.

x12=512

x12=512

Since the expression on each side of the equation has the same denominator, the numerators must be equal.

x=5

Solve for x 1/6x-1/12*(x-1)=1/2